2019
DOI: 10.1002/pat.4695
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between phosphorus tailings and aluminum hypophosphite in flame‐retardant thermoplastic polyurethane composites

Abstract: The massive accumulation of phosphorus tailings (PT) not only occupies land resources and also causes great threat to ecological environment and human security.It is of great significance to explore the resource utilization of PT in some fields. Herein, aluminum hypophosphite (AHP) and PT are blended together to enhance the flame retardancy of thermoplastic polyurethane (TPU) composites, and the synergistic effects between AHP and PT are investigated systematically. Cone calorimeter test (CCT) results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…27 AHP is usually combined with other flame retardants to obtain better flame retardant performance. [28][29][30][31] Zhou et al 32 added AHP and phosphate tailings (PT) into TPU to enhance fire performance of TPU composites. The results confirmed that the peak heat release rate (PHRR), total heat release rate (THRR) and peak smoke production rate (P-SPR) of TPU/AHP22.5/PT2.5 were 91.2%, 69.9%, and 50.9% decreased compared with those of pure TPU, indicating excellent fire retarding performance of AHP/PT synergistic system.…”
Section: Thermal Decomposition Products Of Ahp Can Promotementioning
confidence: 99%
“…27 AHP is usually combined with other flame retardants to obtain better flame retardant performance. [28][29][30][31] Zhou et al 32 added AHP and phosphate tailings (PT) into TPU to enhance fire performance of TPU composites. The results confirmed that the peak heat release rate (PHRR), total heat release rate (THRR) and peak smoke production rate (P-SPR) of TPU/AHP22.5/PT2.5 were 91.2%, 69.9%, and 50.9% decreased compared with those of pure TPU, indicating excellent fire retarding performance of AHP/PT synergistic system.…”
Section: Thermal Decomposition Products Of Ahp Can Promotementioning
confidence: 99%
“…Metal hypophosphate, as a novel flame retardant, is widely used in enhancing fire performance of polymers, including polylactides, thermoplastic polyurethane, and polyamide (Tang et al, 2012;Zhou et al, 2019;Pan et al, 2020). Tang et al report flame retarded polyurethane foam composites based on aluminum diethylphosphinate (ADP), in which 30 php ADP loading makes RPUF composites possess LOI of 23.0 vol% .…”
Section: Introductionmentioning
confidence: 99%
“…To the contrary, non-burning hetero atoms, such as N-, P-, S-, Si-, and B-containing derivative compounds can efficiently reduce flammability when incorporated into the polymer main chain or copolymerized. [19][20][21][22][23][24] Besides, a series of important halogen-free flame retardant systems are applied in the flame retardant of PU, including ammonium polyphosphate (APP), 25 aluminum hypophosphite (AHP), 26 melamine pyrophosphate (MPP), 27 expandable graphite (EG), 28 2D materials [29][30] et al Thereinto, phosphorus plays the important role in halogen-free flame retardancy due to its chemical versatility, multiple FR mechanisms, and high effectivity already at lower loadings.…”
Section: Introductionmentioning
confidence: 99%